EARPC – Energy Aware Routing Protocol for Cooperative MIMO Scheme in WSNs - Kummathi Chenna Reddy; Geetha D. Devanagavi; Thippeswamy M. N. (Journal of Telecommunications and Information Technology, 2020)
Wireless sensor networks are typically operated on batteries. Therefore, in order to prolong network lifetime, an energy eﬃcient routing algorithm is required. In this paper, an energy-aware routing protocol for the co-operative MIMO scheme in WSNs (EARPC) is presented. It is based on an improved cluster head selection method that considers the remaining energy level of a node and recent energy consumption of all nodes. This means that sensor nodes with lower energy levels are less likely to be chosen as cluster heads. Next, based on the cooperative node selection in each cluster, a virtual MIMO array is created, reducing uneven distribution of clusters. Simulation results show that the proposed routing protocol may reduce energy consumption and improve network lifetime compared with the LEACH protocol